Differences between Depression Episodes of Bipolar Disorder I and II - Leman Inanc; Sermin Kesebir; Gonul Yildirim (Psikiyatride Güncel Yaklaşımlar, 2013)
In 1975 Fieve and Dunner made the distinction between hypomania and mania as hypomania does not usually cause social and occupational impair-ment and hospitalization is not needed, moreover patients do not experience psychosis. Bipolar disorder type I is defined by the presence of manic and depressive episodes and differs from Bipolar disorder type II characterized with hipomanic and depressive episodes. Bipolar disorder type I and II do not differ in their depressive episodes. It is still point of contention whether bipolar type II is a variant of bipolar disorder type I or is positioned on the spectrum between bipolar type I and unipolar disorder. Even there are some similarities in characteristics of depressive episodes and outcome features of different bipolar disorder subtypes, there are differences that can be useful in differential diagnosis and treatment. This paper aims to focus on those differences between bipolar disorder type I and II.